All of us villains - Foody, Amanda; Herman, Christine Lynn; Foody, Amanda (New York Tor Teen, 2021)
Every generation, seven families select a champion to compete in a tournament to the death for control of high magick--the most powerful resource in the world--but this year, a salacious tell-all book draws reporters, tourists, and government agents to Ilvernath to watch the bloody curse unfold and some of the champions are determined to thwart their destinies and rewrite their stories.
"A Tom Doherty Associates book."
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Blessing and cursing -- Fiction; Contests -- Fiction; Death -- Fiction; Magic -- Fiction; Survival -- Fiction; Winning and losing -- Fiction